(untitled) (Eurasian Medical Research Periodical, 2024)
Chronic cholecystitis is a disease characterized by inflammation of the gallbladder wall. Women suffer from this disease 3-4 times more often than men, it is most often found in people with excessive body weight, but it is not exceptionally rare in persons of asthenic physique